Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12889-023-15819-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of undiagnosed type 2 diabetes and pre-diabetes among adult Egyptians: a community-based survey

Abstract: Background The global prevalence of abnormal glycemic level comprising diabetes mellitus (DM) and pre-diabetes (PDM) is rapidly increasing with special concern for the entity silent or undiagnosed diabetes; those unaware of their condition. Identification of people at risk became much easier with the use of risk charts than the traditional methods. The current study aimed to conduct a community-based screening for T2DM to estimate the prevalence of undiagnosed DM and to assess the AUSDRISK Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The current study showed that among the studied group, the prevalence of prediabetes was 60/580 (10.3%) and diabetes was 220/580 (37.9%), and the rest had normal diabetes according to the HbA1c test based on ADA standards. However, Farag et al (10) in a crosssectional study from Egypt revealed that the occurrence of diabetes mellitus & pre-diabetes (pre-DM) was 5% & 21.7% respectively, among a group of 719 persons aged eighteen or older. The difference in prevalence may be due to differences in sample size, mean age, physical activity, and other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that among the studied group, the prevalence of prediabetes was 60/580 (10.3%) and diabetes was 220/580 (37.9%), and the rest had normal diabetes according to the HbA1c test based on ADA standards. However, Farag et al (10) in a crosssectional study from Egypt revealed that the occurrence of diabetes mellitus & pre-diabetes (pre-DM) was 5% & 21.7% respectively, among a group of 719 persons aged eighteen or older. The difference in prevalence may be due to differences in sample size, mean age, physical activity, and other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of prediabetes is reversible, and effective intervention is important for the outcome of patients with prediabetes[ 21 ]. Weight loss can reduce or even reverse ectopic deposition and reduce progression of prediabetes to T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents were asked about associated comorbidities, such as hypertension, thyroid issues, renal disease, liver disease, ischemic heart disease, chronic obstructive airway disease, cerebrovascular disease, and autoimmune disease. The second section included the validated Arabic version of the AUSDRISK tool [18], which assesses nine risk factors: age, sex, family history of diabetes, history of high blood glucose, hypertension, smoking, fruit and vegetable intake, physical activity, and waist circumference (Table 1). The sensitivity and specificity of the Arabic version of AUSDRISK at a cut-off point of 13 were 86.11% and 73.35%, respectively, with a 0.887 (95% confidence interval (CI): 0.824-0.95) area under the curve (AUC), p < 0.001.…”
Section: Data Collectionmentioning
confidence: 99%
“…The sensitivity and specificity of the Arabic version of AUSDRISK at a cut-off point of 13 were 86.11% and 73.35%, respectively, with a 0.887 (95% confidence interval (CI): 0.824-0.95) area under the curve (AUC), p < 0.001. Sensitivity and specificity for the detection of abnormal hyperglycemia levels were at a cut-off point of 9 with an AUC of 0.767 (CI: 0.727-0.807), p < 0.001 [18]. Anthropometric measurements: To measure waist circumference, assessors gently surrounded the waist of the respondent with measuring tape, positioning it at the level of the top of the hip bone.…”
Section: Data Collectionmentioning
confidence: 99%